2015
DOI: 10.1111/nph.13265
|View full text |Cite
|
Sign up to set email alerts
|

Slow recovery of High Arctic heath communities from nitrogen enrichment

Abstract: SummaryArctic ecosystems are strongly nutrient limited and exhibit dramatic responses to nitrogen (N) enrichment, the reversibility of which is unknown. This study uniquely assesses the potential for tundra heath to recover from N deposition and the influence of phosphorus (P) availability on recovery.We revisited an experiment in Svalbard, established in 1991, in which N was applied at rates representing atmospheric N deposition in Europe (10 and 50 kg N ha À1 yr À1 ; 'low' and 'high', respectively) for 3-8 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…Both of these experiments showed species composition significantly different to untreated controls and in the C. tetragona dominated heathland lichen cover remained significantly different too. Whilst N concentrations in shrub tissues showed no significant difference from untreated controls, levels in bryophytes remained elevated (Street et al, 2015). In a reciprocal transplant experiment where turfs of R. lanuginosum were relocated from sites with deposition between 8.2 and 32.9 kg N ha − 1 yr −1 to a site with 7.2 kg N ha −1 yr − 1 cover and depth of R. lanuginosum showed no significant difference to the source site controls but biomass was significantly higher than the controls.…”
Section: Impacts Of N Reduction In Heathlandsmentioning
confidence: 76%
See 1 more Smart Citation
“…Both of these experiments showed species composition significantly different to untreated controls and in the C. tetragona dominated heathland lichen cover remained significantly different too. Whilst N concentrations in shrub tissues showed no significant difference from untreated controls, levels in bryophytes remained elevated (Street et al, 2015). In a reciprocal transplant experiment where turfs of R. lanuginosum were relocated from sites with deposition between 8.2 and 32.9 kg N ha − 1 yr −1 to a site with 7.2 kg N ha −1 yr − 1 cover and depth of R. lanuginosum showed no significant difference to the source site controls but biomass was significantly higher than the controls.…”
Section: Impacts Of N Reduction In Heathlandsmentioning
confidence: 76%
“…Species composition and richness generally seem to be slow to recover with some long-term investigations still showing differences after a decade or more (e.g. Stevens et al, 2012a;Street et al, 2015;Strengbom et al, 2001). This is not the case for all long-term investigations, Storkey et al (2015) reported changes in species composition of control plots of the Park Grass experiment which could be correlated with changes in N deposition.…”
Section: Impacts Of N Reduction In Wetlandsmentioning
confidence: 99%
“…, Street et al. ) suggesting colimitation in some instances. However, the soils in this region are volcanic in origin with andic properties including relatively high P and water retention capacity (Arnalds ).…”
Section: Discussionmentioning
confidence: 97%
“…Based on these results they could not rule out ecological impacts from even relatively small increases in reactive N deposition in such ecosystems. Recently, Street et al (2015) uniquely assessed the potential for tundra heath to recover from N deposition and the influence of phosphorus (P) availability on recovery based on an experimental site in Svalbard. The empirical critical load of N for tundra is set at 3-5 kg N ha-1 yr-1 (Bobbink & Hettelingh 2011).…”
Section: Vulnerabilitymentioning
confidence: 99%
“…Importantly, N + P has caused dramatically increased moss abundance, which influences nutrient dynamics. Street et al (2015) finally concluded that Arctic ecosystems are slow to recover from even small N inputs, particularly where P is not limiting. Hence, fragile and nutrient limited ecosystems in mountains and in the Arctic and Polar regions should be considered as vulnerable and included in future monitoring systems.…”
Section: Vulnerabilitymentioning
confidence: 99%